IL-21: A Pleiotropic Cytokine with Potential Applications in Oncology - Michela Croce; Valentina Rigo; Silvano Ferrini (Journal of Immunology Research, 2015)
Interleukin- (IL-) 21 is a pleiotropic cytokine that regulates the activity of both innate and specific immunity. Indeed, it costimulates T and natural killer (NK) cell proliferation and function and regulates B cell survival and differentiation and the function of dendritic cells. In addition, IL-21 exerts divergent effects on different lymphoid cell leukemia and lymphomas, as it may support cell proliferation or on the contrary induce growth arrest or apoptosis of the neoplastic lymphoid cells. Several preclinical studies showed that IL-21 has antitumor activity in different tumor models, through mechanism involving the activation of NK and T or B cell responses. Moreover, IL-21’s antitumor activity can be potentiated by its combination with other immune-enhancing molecules, monoclonal antibodies recognizing tumor antigens, chemotherapy, or molecular targeted agents. Clinical phase I-II studies of IL-21 in cancer patients showed immune stimulatory properties, acceptable toxicity profile, and antitumor effects in a fraction of patients. In view of its tolerability, IL-21 is also suitable for combinational therapeutic regimens with other agents. This review will summarize the biological functions of IL-21, and address its role in lymphoid malignancies and preclinical and clinical studies of cancer immunotherapy.